170k views
2 votes
F(x) = x2 - 4.
Find the inverse of the function

User Slaporte
by
6.0k points

1 Answer

0 votes

Answer:


f^(-1)(x) = √ x + 4

Explanation:

step 1) replace f(x) with y

y = x² - 4

step 2) switch the x and y (because every (x, y) has a (y, x))

x = y² - 4

step 3) add 4 to both sides of the equal sign

x + 4 = y²

step 4) take the square root of both sides of the equal sign (the square root symbol cancels out the ²)

√ x + 4 = y

step 5) you know have the inverse of f(x) = x² - 4


f^(-1)(x) = √ x + 4

User Petro Franko
by
6.2k points